Analysis of natural circulation operational characteristics for integrated pressurized water reactor. (June 2016) - Xia, G.L.; Su, G.H.; Peng, M.J.
Highlights: We study the conversion process from forced circulation to natural circulation of IPWR. Improved control strategy can weaken reactor power oscillation during conversion process. Stable operation boundary was determined at natural circulation conditions. IPWR can restore to steady state operation quickly under natural circulation conditions. Abstract: The present work discusses the natural circulation operational characteristics of integrated pressurized water reactor (IPWR). A thermal hydraulic model of IPWR was established using RELAP5 code. Under the ideal steady-state control scheme, IPWR can realize the reactor power change with steam flow. The conversion process from forced circulation to natural circulation has been studied. The results show that the reactor power has large fluctuations during the conversion process based on the traditional control scheme. Two optimized control schemes were applied to achieve a smooth conversion process. From the perspective of reducing power oscillation, the result obtained by canceling the reactor power control at initial conversion process is better than the results obtained by shutting down each pump one by one. Under natural circulation conditions, the stable operation boundary of IPWR system was determined. The steady state operation characteristics and rapid load change process under natural circulation show that primary coolant can achieve stable natural circulation operation at low load conditions. The obtained analysis results are significant for improving operation characteristics of the IPWR.